Improved singlet oxygen yields of new palladium phthalocyanines using sonochemistry and comparisons with photochemistry - Karanlik, Ceren Can; Atmaca, Goknur Yasa; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Sono-photodynamic therapy (SPDT) is a new approach for the determination of singlet oxygen quantum yields in non-invasively solid tumor studies. In SPDT application, effective tissue penetration is much more than that occurring in conventional photodynamic therapy (PDT) application. On the other hand, due to the synthetic difficulty of palladium phthalocyanines, there are few numbers of literature studying the unique properties of palladium phthalocyanines. For these reasons, this study presents the synthesis of three new non-peripherally substituted palladium(II) phthalocyanine complexes (PdPc1, PdPc2 and PdPc3). All the resulting compounds were characterized using FT-IR, H-1-NMR and mass spectroscopic methods. Also, this study comparatively focuses on both photochemical and sono-photochemical methods to examine the photophysicochemical properties of the newly synthesized palladium phthalocyanine complexes (PdPcs) for the first time. For the stated PdPcs, lower singlet oxygen yields were obtained by applying the photochemical method compared to those obtained by performing the sono-photochemical method. In the photochemical study, the respective singlet oxygen values (Phi(Delta)) of the phthalocyanine complexes (PdPc1-3) were obtained 0.45, 0.51 and 0.70 while in the sono-photochemical study, the singlet oxygen values (Phi(Delta)) were obtained 0.71, 0.75 and 0.82, respectively. These results indicated that the sono-photochemical method is a more promising approach than the photochemical one.
Keywords: Sono-photochemical; Photochemical; Palladium phthalocyanine; Singlet oxygen; PHENOXY; Chemistry; Crystallography